2010
DOI: 10.1111/j.1551-2916.2010.03648.x
|View full text |Cite
|
Sign up to set email alerts
|

Doping of BiScO3–PbTiO3 Ceramics for Enhanced Properties

Abstract: High-temperature piezoelectrics are a key technology for aeronautics and aerospace applications such as fuel modulation to increase the engine efficiency and decrease emissions. The principal challenge for the insertion of piezoelectric materials is the limitation on upper use temperature which is due to low Curie-Temperature (T C ) and increasing electrical conductivity. BiScO 3 -PbTiO 3 (BS-PT) system is a promising candidate for improving the operating temperature for piezoelectric actuators due to its high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
(62 reference statements)
3
22
1
Order By: Relevance
“…Higher peaks current of S13 and S23 are observed, indicating more domain walls switching under coercive field, which is consistent with the observation of higher piezoelectric coefficient of S13 and S23. All samples show square hysteresis loops as a result of A-site vacancies effect which was proposed by Sehirlioglu et al [19]. This is consistent with the observation of EDS which indicated that all grains were of Bi-, Pb-deficiency.…”
Section: Electrical Characterizationsupporting
confidence: 88%
“…Higher peaks current of S13 and S23 are observed, indicating more domain walls switching under coercive field, which is consistent with the observation of higher piezoelectric coefficient of S13 and S23. All samples show square hysteresis loops as a result of A-site vacancies effect which was proposed by Sehirlioglu et al [19]. This is consistent with the observation of EDS which indicated that all grains were of Bi-, Pb-deficiency.…”
Section: Electrical Characterizationsupporting
confidence: 88%
“…At the saturation state of the polarization (Fig. 4a), the P r and E c of the BS-PT-II ceramic sintered at 1000 C for 2 h are 43.2 mC/cm 2 and 30.9 kV/cm, respectively, higher than the previously reported values [5][6][7][8][9]15,16,26,27,30]. The switching current-electric field curve exhibits two slightly asymmetric peaks with peaks value 10 and À12 A/m 2 , respectively.…”
Section: Methodscontrasting
confidence: 43%
“…The strain behavior results indicate a bipolar strain of 0.4% and a unipolar strain of 0.23% (Fig. 4b and c), respectively, both again higher than previously reported values [5][6][7][8]15,26,27,30].…”
Section: Methodssupporting
confidence: 41%
“…found an increase in T C with a decrease in B‐site cationic radii for B′ = Sc (BS), In (BI), and Yb (BY). At the MPB composition (0.64 PT–0.36 BS), BS exhibited a high T C = 450°C, high piezoelectric coefficients d 33 = 335–450 pC/N, and high coupling factors k p = 0.55 close to that of PZT . Also observed in this system was a temperature independent MPB up to 300°C suggesting a wide range of temperature stability similar to PZT .…”
Section: Introductionmentioning
confidence: 82%